Retraction: The Comparison of The Effectiveness Back Massage with Clary Sage Essential Oil and Postpartum Exercise for Post Partum Uterus Involution (J. Phys.: Conf. Ser.1114 012009). (7th February 2019) - Azizah, Nurul; Rosydah, Rafhani; Mahfudloh, Hanik
Abstract: This paper was retracted by IOP Publishing on 12 December 2018. This paper was published due to a technical error and was not intended to be included in this journal. Retraction published: 8 February 2019